ANALISIS UI/UX PADA DESAIN OASE MENGGUNAKAN METODE HEURISTICEVALUATION DAN WEBUSE - Putra Sentana, Kadek Wibawa; Faridzky, Fadel; Sudarma, Made; Suyadnya, I Made Arsa; Khrisne, Duman Care (Peneliti.net, 2024)
Learning Management System (LMS) is a system to manage learning and lecturer-student interaction. Udayana University has an LMS called OASE, which supports online and blended learning. OASE has some UI/UX issues such as login problem, rigid interface, and slow upload. UI/UX usage is important for website performance. UI/UX analysis involves Heuristic Evaluation and WEBUSE. Heuristic Evaluation focuses on appearance, while WEBUSE on user experience. OASE analysis with these methods aims to improve performance and measure UI/UX. This research aims to analyze the User Interface (UI) and User Experience (UX) of the OASE e-learning service at Udayana University Bali. The methods used in this research are Heuristic Evaluation and WebUSE to identify potential problems and assess user satisfaction in using the e-learning platform. The results of this evaluation will identify errors or problems that exist in layout, navigation, interaction, and other design aspects. Furthermore, a WEBUSE analysis was conducted by collecting data from users of the OASE e-learning service. The participants involved in this research are students and lecturers who have used OASE. The results of this research will provide a comprehensive picture of potential problems in the UI/UX of the OASE e-learning service at Udayana University Bali. The findings of the Heuristic Evaluation will serve as a guide for design improvements, while the WebUSE analysis will provide insights into user preferences for further improvements.